Health impact of disinfection by-products in swimming pools - Cristina M. Villanueva; Laia Font-Ribera (Istituto Superiore di Sanità, 2012)
This article is focused on the epidemiological evidence on the health impacts related to disinfection by-products (DBPs) in swimming pools, which is a chemical hazard generated as an undesired consequence to reduce the microbial pathogens. Specific DBPs are carcinogenic, fetotoxic and/or irritant to the airways according to experimental studies. Epidemiological evidence shows that swimming in pools during pregnancy is not associated with an increased risk of reproductive outcomes. An epidemiological study suggested an increased risk of bladder cancer with swimming pool attendance, although evidence is inconclusive. A higher prevalence of respiratory symptoms including asthma is found among swimming pool workers and elite swimmers, although the causality of this association is unclear. The body of evidence in children indicates that asthma is not increased by swimming pool attendance. Overall, the available knowledge suggests that the health benefits of swimming outweigh the potential health risks of chemical contamination. However, the positive effects of swimming should be enhanced by minimising potential risks.